Automation of the Export Data from Open Journal Systems to the Russian Science Citation Index - Семеріков, Сергій; Потоцький, Владислав; Словак, Катерина; Грищенко, Світлана; Ків, Арнольд (Pedagogy of Higher and Secondary Education, 2018)
Semerikov S.O. Pototskyi V.S., Slovak K.I., Hryshchenko S.M. and Kiv A.E. Automation of the Export Data from Open Journal Systems to the Russian Science Citation Index. It is shown that the calculation of scientometric indicators of the scientist and also the scientific journal continues to be an actual problem nowadays. It is revealed that the leading scientometric databases have the capabilities of automated metadata collection from the scientific journal website by the use of specialized electronic document management systems, in particular Open Journal Systems. It is established that Open Journal Systems successfully exports metadata about an article from scientific journals to scientometric databases Scopus, Web of Science and Google Scholar. However, there is no standard method of export from Open Journal Systems to such scientometric databases as the Russian Science Citation Index and Index Copernicus, which determined the need for research. The aim of the study is to develop the plug-in to the Open Journal Systems for the export of data from this system to scientometric database Russian Science Citation Index. As a result of the study, an infological model for exporting metadata from Open Journal Systems to the Russian Science Citation Index was proposed. The SirenExpo plug-in was developed to export data from Open Journal Systems to the Russian Science Citation Index by the use of the Articulus release preparation system.